A Case of Drug-induced Cutaneous Toxicity Observed in Cynomolgus Monkeys. (June 2016) - Kikkawa, Rie
The purpose of this article is to describe a case of drug-induced cutaneous toxicity observed in cynomolgus monkeys and to introduce approaches attempted in order to elucidate mechanisms. The test article was a small molecule with a ubiquitously distributed target, especially in rapidly dividing cells, and which modulated cell cycle regulation. After 7 consecutive days of oral dosing, animals developed multifocal skin lesions. The lesions were characterized clinically by vesicles and scabs formation and were distributed mainly in thin-skinned areas of the body including the cheek, chest, abdomen, and inner limbs. Microscopically, the lesions were confirmed as epidermal vesicle formation and ulceration. Immunohistochemical staining revealed that the levels within the epidermis where separation (vesicle formation) occurred were not consistent. The differential diagnoses for vesicular skin lesions and our efforts to elucidate the mechanism of toxicity using in-house database searches and immunohistochemistry are discussed. To the best of our knowledge, similar cutaneous toxicity has not been reported previously, although there are reports of other types of cutaneous toxicities. Understanding the mechanisms of the toxicity is very important when assessing human relevancy during drug development. Our investigative approach can be utilized when unusual skin toxicities are observed in the future.